Clinical approaches for poststroke seizure: a review - Ryu, Han Uk; Kim, Hong Jin; Shin, Byoung-Soo; Kang, Hyun Goo (Frontiers in Neurology, 2024)
Poststroke seizure is a potential complication of stroke, which is the most frequent acute symptomatic seizure in adults. Patients with stroke may present with an abnormal or aggressive behavior accompanied by altered mental status and symptoms, such as hemiparesis, dysarthria, and sensory deficits. Although stroke manifestations that mimic seizures are rare, diagnosing poststroke seizures can be challenging when accompanied with negative postictal symptoms. Differential diagnoses of poststroke seizures include movement disorders, syncope, and functional (nonepileptic) seizures, which may present with symptoms similar to seizures. Furthermore, it is important to determine whether poststroke seizures occur early or late. Seizures occurring within and after 7 d of stroke onset were classified as early and late seizures, respectively. Early seizures have the same clinical course as acute symptomatic seizures; they rarely recur or require long-term antiseizure medication. Conversely, late seizures are associated with a risk of recurrence similar to that of unprovoked seizures in a patient with a focal lesion, thereby requiring long-term administration of antiseizure medication. After diagnosis, concerns regarding treatment strategies, treatment duration, and administration of primary and secondary prophylaxis often arise. Antiseizure medication decisions for the initiation of short-term primary and long-term secondary seizure prophylaxis should be considered for patients with stroke. Antiseizure drugs such as lamotrigine, carbamazepine, lacosamide, levetiracetam, phenytoin, and valproate may be administered. Poststroke seizures should be diagnosed systematically through history with differential diagnosis; in addition, classifying them as early or late seizures can help to determine treatment strategies.